Whole-genome sequencing of Hyphopichia burtonii from isolated yeast recovered from zebra dove droppings in Thailand - Saowakon Indoung; Sanicha Chumtong; Sakaoporn Prachantasena; Ratchakul Wiriyaprom; Komwit Surachat; Rattanaruji Pomwised; Ruttayaporn Ngasaman (PLoS ONE, 2025)
This study aimed to characterize zoonotic yeasts from zebra dove (Geopelia striata) droppings in small farms in Songkhla province, Thailand. Four out of thirty-one isolates were found with morphology and biochemical test results like those of Cryptococcus spp. (12.9%) but they exhibited different results from the positive control in nested polymerase chain reaction (PCR); the first step with ITS1-ITS4 primers was negative, but the nested PCR step with CN4-CN5 was positive. All isolates were subjected to antifungal susceptibility testing. Only the Tip11 isolate showed high resistance to itraconazole and ketoconazole, with minimum inhibitory concentrations of >32.0 and 32.0 µg/mL, respectively, corresponding to high levels of minimum fungicidal concentrations for both drugs (>32 µg/mL). Consequently, Tip11 was selected as a representative of the contaminated isolates and subjected to whole-genome sequencing analysis. The results identified the Tip11 isolate as Hyphopichia burtonii (99.30% identity), with a genome length of 12,360,159 bp, a GC content of 35.16%, and 2,146 protein groups closely related to the Saccharomycetaceae family. It showed 43 candidates resistance genes of antifungal drugs mostly in azole and itraconazole group which related to the antifungal susceptibility testing. This is the first report of H. burtonii in zebra doves in Thailand. This yeast has been previously identified as a cause of human infection leading to peritonitis in Thailand, and its resistance to antifungal drugs may pose a public health risk. Therefore, the application of biosecurity measures on farms, such as regular removal of droppings and cage sanitization, should be implemented according to good agricultural practices.